Partial Analysis of Probiotic Character of Lactic Acid Bacteria from the Intestines of Broilers Supplemented with Fish Protein Hydrolysate (FPH) - Nashrullah, Shafa; Utami, Eva Tyas; Purniasari, Fina Yunita; Anggitasari, Dhanti Fatma; Utarti, Esti (Jurnal ILMU DASAR, 2025)
This study aims to analyze partial characteristics of probiotics lactic acid bacteria (LAB) from broiler intestines supplemented with fish protein hydrolysate (FPH) 2% (v/w) in feed. A total of 17 LAB isolates were successfully isolated and characterized morphologically and biochemically (catalase test). The isolate showed diverse morphological and biochemical properties, obtained as many as seven isolates that met the partial characteristics of probiotics, namely U10, U11, U13, U16, U31, U33, and U37 which were Gram-positive and no endospores and catalase formations were found. The tolerance test for acid pH and NaCl performed on the seven BAL isolates showed a diverse survival rate with U11 showing the highest tolerance at pH 2 (11.4%) and NaCl concentration up to 8% (32.4%). These findings highlight seven LAB isolates with partial probiotic properties, providing new insights into the development of probiotic candidates from broiler guts to improve gastrointestinal health and productivity.